Feeding Issues and Interventions in Infants and Children with Clefts Lip and Palate: A Meta-Analysis - Resina Putri, Anggi; Roy Romey Daulas Mangunsong (PT Inovasi Pratama Internasional, 2025)
The feeding process in infants with cleft lip and palate is greatly influenced by the ability to suck and swallow. Infants with this condition often have difficulty in sucking and swallowing effectively, which can lead to longer feeding duration, fatigue in the infant, risk of aspiration, and decreased nutritional intake. Inefficient oral feeding can inhibit the growth and development of the infant. Therefore, feeding infants with cleft lip and/or palate requires great care and knowledge from the mother. If not treated quickly and appropriately, this condition can cause malnutrition, growth retardation, and other health complications. This study aims to determine the description of feeding and intervention in infants with cleft lip and palate. The method used is meta-analysis, with a range of articles selected from 2015 to 2025. Article searches were carried out systematically and comprehensively through the PubMed, Science Direct, Elsevier, and Google Scholar databases, using the PICO (Population, Intervention, Comparison, Outcome) model to determine the eligibility of the article. Articles that met the qualitative criteria were reviewed again, and from this process six articles were obtained that were eligible for quantitative analysis. This meta-analysis showed that infants and children with cleft lip and palate had lower developmental outcomes than those without the condition (effect value -0.41; 95% CI = -0.29 to 0.01). The six primary studies were from countries such as South Africa, the United States, Brazil, and Italy, and were cross-sectional in design.